Framework of property rating practice for financing neighbourhood facilities provision in Nigeria - Baba, Habu Mallam (2017)
This study proposed a framework of property rating practice for financing neighbourhood facilities provision in Bauchi metropolis of Nigeria. The deplorable condition of neighbourhood facilities in the study area persists, while the existing initiative aimed at maintaining and redeveloping the community facilities has not been implemented. This study examined the existing condition of neighbourhood facilities in the study area, and evaluated the most significant factors that militated against the implementation of property rating practice for financing neighbourhood facilities provision. The study has collected quantitative data, and used SPSS for the descriptive analysis, reliability analysis and exploratory factor analysis; and applied Structural Equation Modelling (SEM) with Analysis of Moment Structure (AMOS) for the analyses of the measurement and the structural measurement models. Findings revealed that Over-Reliance on Crude Oil Revenue and Poor Taxation System are the most significant factors militating against the implementation of property rating practice in Bauchi metropolis. And that ‘lack of political will’ is a factor that significantly affects the existing condition of neighbourhood facilities in the study area. In conclusion the study has proposed Land area-based assessment for rating valuation, using Google Earth/Map for property identification, enumeration and measurement in the proposed framework in order to achieved cost-effectiveness in assessment. The significant contribution is that, the study has proposed a new costeffective framework of Property Rating Practice for financing neighbourhood facilities in the study area. It was recommended that the government should diversify revenue source from oil-based to harness all avenues like property rating at municipal level so as to finance neighbourhood facilities provision and maintenance. Future studies should find out, apart from Over Reliance on Crude Oil Revenue and Poor Taxation System, whether some other factors militate against the implementation of property rating in the study area and beyond.